Palisade cartilage fascia tympanoplasty: our experience - Lambor, Dheeraj; Bhuskute, Govind; Barreto, Ombretta (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Cartilage tympanoplasty is one of the procedures performed for treatment of tympanic membrane perforation, more so in those cases associated with eustachian tube dysfunction, or failed previous temporalis fascia type 1 tympanoplasty. Palisade cartilage tympanoplasty, initially described by Heerman utilizes strips of conchal cartilage to reconstruct the tympanic membrane. Methods: A retrospective study which was presented with 64 patients who underwent palisade cartilage- fascia type I tympanoplasty and compared their hearing outcome after three years of post-operative period. Indication to perform a cartilage-fascia tympanoplasty was either an atelectatic middle ear or large perforation of the drum or residual or recurrent perforation following previous temporalis fascia myringoplasty. Results: Average pre-operative hearing loss was 37.38±15.04 dB, while post-operative hearing loss was 20.47±8.85 dB, giving an average gain of 17.03 dB. Of 64 patients, 93.7% patients had fully healed neotympanum. Conclusions: Palisade cartilage fascia tympanoplasty is an effective method to ensure graft uptake and at the same time achieve competitive hearing gain. The reliability of this technique lies in its use for recurrent and residual perforations of the tympanic membrane as well as in cases associated with eustachian tube dysfunction.